Pemberdayaan Petani Melalui Penyuluhan Kesehatan dan Keselamatan Kerja (K3) Di Desa Pucak, Kec. Tompobulu, Kab. Maros - Hamzah, Wardiah; Batara, Andi Surahman; Syam, Nasruddin (PT.Mantaya Idea Batara, 2023)
Farmers who are physically and mentally healthy will increase work productivity, thereby increasing the welfare of their families. An unergonomic working position for farmers while working can cause fatigue, injury and work accidents. Problems of farmers in Pucak Village, Kec. Tompobulu as a partner namely; do not know the impact of fatigue and work accidents, do not know and measure ergonomic work positions, and do not do gymnastics and ergonomic work positions before work. The solutions offered are: (1) Counseling on work fatigue and accidents, (2) Measurement of ergonomic work positions and (3) Exercise training and ergonomic work positions. The results of the activity are (1) increased knowledge about the effects of fatigue and work accidents, (2) the working position of farmers is generally at risk of experiencing musculoskeletal disorders. Farmers also know ergonomic work positions, as well as (3) ergonomic exercises before work and ergonomic positions when working according to farmers' conditions. It is recommended that cross-sectoral involvement in creating a Safety Farming Village, training in providing first aid for musculoskeletal disorders.